Technological change, technical and allocative efficiency in Chinese agriculture: the case of rice production in Jiangsu - Fan, Shenggen (International Food Policy Research Institute, 1999)
This paper develops a frontier shadow cost function approach to estimate empirically the effects of technological change, technical and allocative efficiency improvement in Chinese agriculture during the reform period (1980-93). The results reveal that the first phase rural reforms (1979-84) which focused on the decentralization of the production system have had significant impact on technical efficiency but not allocative efficiency. During the second phase reforms which was supposed to focus on the liberalization of rural markets, technical efficiency improved very little and allocative efficiency has increased only slightly, however. In contrast, the rate of technological change continued to increase, although at a declining rate during the second phase reform.